Les concepts de convertibilite selon le Fonds. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1971)
This paper examines the IMF's concepts of convertibility and gives some impression of their purposes. The central concept of convertibility in the Articles is the convertibility of Article VIII, Sections 2, 3, and 4. Under it, the basic rule is that members must avoid restrictions on the making of payments and transfers for current international transactions, multiple currency practices, and discriminatory currency arrangements. In addition, a member that has accepted the obligations of Article VIII must convert balances of its currency in certain circumstances when those balances are presented for conversion by the monetary authorities of another member.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet